Hydrothermal organic aggregates associated with the high-Ni grades of the Cerro Matoso laterite deposit, Montelíbano, Colombia. - Castrillón Peña, Andrés; Cramer, Thomas Heinrich; Guerrero, Javier (Ofioliti, 2022)
Mineralogical and geochemical analyses (EDS, ICP-MS, XRD) of black mudstones locally overlying the peridotites of Cerro Matoso at Pit-1 link these sediments with deep-sea hydrothermal systems. In this unit, rounded particles were identified that would correspond with organic aggregates commonly found in reducing environments related to hydrothermal vent systems. These aggregates are formed by methane-producing microorganism (methanogens) metabolism that sustains such extreme environments mediated by anaerobic methane-consuming cell consortia. The organic aggregates register Ni content up to 8 wt%. For this fossilized methanogen-AOM (Anaerobic Oxidation of Methane) consortium we propose an ultramafic contribution, followed by a hydrothermal enrichment of Black/White-Smoker type and a supplementary contribution of bio-mineralized Ni of the organics within the sediments during the formation of the Ni-bearing deposit. The sediments configured an atypical lateritic profile at the Pit-1 where Ni-concentrations reached up to 8 wt%, in contrast to the southern Pit-2 where the peridotites developed a typical lateritic profile with nickel concentrations not exceeding 4 wt%. During the Cretaceous and Cenozoic, the ultramafic rocks and associated deep-sea hydrothermal-related sediments were accreted to the South American continent. They were recently exhumed allowing supergene Ni-enrichment forming the laterite deposit known today with its locally extraordinary high Ni contents. Together with the organics, authigenic phyllosilicates and Fe-(oxy) hydroxides are the main ‘‘ore minerals” that contributed to add the lateritic Ni-enrichment after supergene leaching processes due to weathering of the Cerro Matoso peridotites.